Tata Ruang dan Perkembangan Kompleks Pabrik Gula Tanjung Tirto Tahun 1920-1944, Kabupaten Sleman - Oktavian Ardana Putra; Niken Wirasanti (Kemendikbud, 2019)
The Tanjung Tirto sugar factory was one of 18 sugar factories that had been established in Yogyakarta during the Dutch East Indies administration. This factory was built in 1874 and was destroyed in the 1940s. The layout and development of the sugar factory from 1920-1940 were discussed in this study. Based on field observations, the emplacement of the factory buildings was not complete and only left a few housing buildings for the former factory employees. In addition, reconstruction through an old map is a way to find out the location and development of this factory. This study is important considering the lack of sugar factories in Yogyakarta which are the object of archeological research studies.